Assessing the Short Term Macroeconomic Impact of the Net Zero Transition - Holmberg, Ulf (International Journal of Economics and Financial Issues, 2023)
A method for assessing the macroeconomic impact of a transition toward carbon neutrality is presented. The method utilizes the long-term global economic gain of the transition, and distributes the global gain to individual countries by using the (implicit) pledges made under the Paris Agreement. By considering the quantified gain as a country’s maximum investment amount, consistent transition-dependent macroeconomic pathways can be assessed. Unsurprisingly, orderly versus delayed and disorderly transitions produce different macroeconomic outcomes, a difference that indicates that there is a macroeconomic aspect to both the risk and the gains of the transition toward carbon neutrality. The method presented can be used for, for example, understanding the macroeconomic risks during the transition phase, which, in turn, can be used for assessing certain macroeconomic aspects of transition risk. This method is flexible and allows for several different transition periods to be studied and can be used to shed light on different aspects of the risks related to the transition toward carbon neutrality.